2014
DOI: 10.1093/cid/ciu313
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin, Metronidazole, or Tolevamer for Clostridium difficile Infection: Results From Two Multinational, Randomized, Controlled Trials

Abstract: Tolevamer was inferior to antibiotic treatment of CDI, and metronidazole was inferior to vancomycin. Trial Registration. clinicaltrials.gov NCT00106509 and NCT00196794.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
368
1
20

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 457 publications
(398 citation statements)
references
References 26 publications
9
368
1
20
Order By: Relevance
“…Metronidazole is commonly used for the treatment of CDI and is guideline recommended for an initial episode of mild-to-moderate CDI (3,11). Observational and clinical trials have observed a decreased clinical cure rate with patients treated with metronidazole; however, the reasons for this decreased response rate are unclear (4)(5)(6)8). In this study, continued use of antibiotics, severe CDI, and a high Horn's index were predictive of patients at higher risk for refractory CDI when given metronidazole.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Metronidazole is commonly used for the treatment of CDI and is guideline recommended for an initial episode of mild-to-moderate CDI (3,11). Observational and clinical trials have observed a decreased clinical cure rate with patients treated with metronidazole; however, the reasons for this decreased response rate are unclear (4)(5)(6)8). In this study, continued use of antibiotics, severe CDI, and a high Horn's index were predictive of patients at higher risk for refractory CDI when given metronidazole.…”
Section: Discussionmentioning
confidence: 71%
“…Oral metronidazole is a treatment option for C. difficile infection (CDI) and is recommended in the guidelines for the treatment of mild-to-moderate disease (3). However, observational (4) and randomized controlled (5,6) studies have demonstrated high clinical failure rates in patients with CDI given metronidazole. Colonic concentrations of metronidazole are relatively low and not predictable, and this drug is not considered by many to be an optimal pharmacologic agent for CDI (7).…”
mentioning
confidence: 99%
“…12 The most significant recent findings are from a pooled analysis of two phase III trials of tolevamer (a toxin binding polymer), which failed to demonstrate equivalence to standard treatment. 13 These data additionally showed that clinical success occurred significantly less often following metronidazole compared to vancomycin therapy (73% and 81%, respectively, p=0.02). 13 However, metronidazole continues as first-line CDI therapy in many countries due to low acquisition cost and the perceived risk of VRE with vancomycin.…”
Section: Current CDI Antibioticsmentioning
confidence: 83%
“…13 These data additionally showed that clinical success occurred significantly less often following metronidazole compared to vancomycin therapy (73% and 81%, respectively, p=0.02). 13 However, metronidazole continues as first-line CDI therapy in many countries due to low acquisition cost and the perceived risk of VRE with vancomycin. [6][7] Oral vancomycin is often recommended for severe or complicated CDI.…”
Section: Current CDI Antibioticsmentioning
confidence: 83%
“…Furthermore, this meta-analysis determined the most effective method of treatment for CDI stratified by disease severity 3 . The most comprehensive study of the meta-analysis was by Johnson, et al, titled "Vancomycin, metronidazole, or tolevamer for Clostridium difficile infection: results from two multinational, randomized, controlled trials," which used two randomized controlled trials to assess treatment efficacy by both primary and secondary outcomes with three different medications, including vancomycin and metronidazole 2 . The meta-analysis contained two other studies that compared the efficacy of metronidazole with vancomycin in patients with severe CDI.…”
Section: Research Articlementioning
confidence: 99%